2009
DOI: 10.1080/10862960802637604
|View full text |Cite
|
Sign up to set email alerts
|

Narrating and Performing Identity: Literacy Specialists' Writing Identities

Abstract: In this study, we explored ways that four literacy specialists who worked in three schools that were part of one state's Reading Excellence Act (REA) grant constructed their identities as writers and as teachers of writing. We also explored how they negotiated the performance of those identities in different contexts over a two-year period. Literacy specialists' writer's autobiographies composed during the first year and interviews conducted near the end of the second year comprised the major data sources that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Self-descriptions ranged from 'love' of writing to 'fearful and reluctant ' (McKinney and Giorgis 2009);'avid' to 'avoider' (Brooks 2007). McKinney and Giorgis (2009) found that teachers narrated diverse writer identities, both writer and non-writer, constructed over time through different life and school experiences. Two studies found that teachers of English/literacy were more likely to present themselves as keen readers than keen writers.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Self-descriptions ranged from 'love' of writing to 'fearful and reluctant ' (McKinney and Giorgis 2009);'avid' to 'avoider' (Brooks 2007). McKinney and Giorgis (2009) found that teachers narrated diverse writer identities, both writer and non-writer, constructed over time through different life and school experiences. Two studies found that teachers of English/literacy were more likely to present themselves as keen readers than keen writers.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…For some prospective teachers, the negative impact was such that as adults they remained fearful of writing and doubted their ability to teach it (Street 2003). For one experienced literacy specialist, memories of school writing were so distressing that she chose not to engage in writing or teach writing to students (McKinney and Giorgis 2009). By contrast, a practising teacher in Cremin and Baker's (2010) study attributed her growth in confidence to a single teacher and his commitment to writing tutorials.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations